Tahajjud Prayer from Psychological and Health Perspectives - Dewi Purnamasari (International Forum of Researchers and Lecturers, 2025)
One of the main sunnah prayers is the night prayer (Tahajud), because the night prayer is one of the mustajab prayers offered by a servant to the Creator, namely those who can wake up at night and pray at night and then perform the prayer service, because the night is the most appropriate time for someone to pray and munajat to perform prayers at night with the highly recommended prayer, namely the Tahajud prayer. The research method used in this article is a library research method with a descriptive qualitative approach. This approach is used to examine and analyze various relevant scientific sources regarding the Tahajjud Prayer in a Psychological and Health Perspective. The results of the study show that the Tahajud Prayer has a significant positive impact on psychological and physical health. Psychologically, Tahajud can increase calm, reduce stress and anxiety, and increase self-confidence and enthusiasm. From a physical health perspective, the Tahajud prayer can help increase endurance, improve blood circulation, and even help overcome digestive disorders.